In vitro leaf inoculation studies as an indication of tree foliage susceptibility to Phytophthora ramorum in the UK - Denman, S.; Kirk, S. A.; Brasier, C. M.; Webber, J. F. (PLANT PATHOLOGY, 2005)
Leaves of 11 coniferous and 23 broad-leaved tree species important to UK forestry were tested for their susceptibility to the quarantine pathogen Phytophthora ramorum using a detached leaf assay. Two European and two USA isolates were used. Wounded and unwounded leaves were dipped in zoospore suspensions during summer; conifers were also tested in winter. Successful infection of tissue and amount of necrosis were assessed. Highly susceptible broad-leaved hosts included Aesculus hippocastanum, Fraxinus excelsior, Quercus ilex, Ulmus procera and, to a lesser extent, Castanea sativa, Q. cerris and Q. petraea, together with Umbellularia californica and rhododendrons. Acer pseudoplatanus, Alnus glutinosa, Carpinus betulus, Corylus avellana, Fagus sylvatica, Prunus avium, Q. robur, Q. rubra and Q. suber showed consistently low susceptibility. Conifer species including Abies procera, Picea abies, P. sitchensis, Pseudotsuga menziesii, Sequoia sempervirens and Tsuga heterophylla were also susceptible. Pseudotsuga menziesii and A. procera were severely affected. Pinus contorta, P. nigra var. maritima and P. sylvestris were virtually resistant, while Taxus baccata was only slightly affected. Increased necrosis was apparent on leaves that were wounded prior to inoculation. These results extend the known range of trees that P. ramorum is able to attack and confirm its relative host-nonspecificity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL
Keywords: broad-leaved species; conifers; detached leaf dip assay; foliage; forest species; sudden oak death

Phytophthora ramorum on Quercus ilex in the United Kingdom. - Denman, S.; Kirk, S. A.; Brasier, C. M.; Barton, V. C.; Hughes, K. J. D.; Webber, J. F. (PLANT DISEASE, 2005)
Phytophthora ramorum causes bleeding cankers of trunks of trees native to the west coast of the United States (i.e., Quercus kelloggii, Q. parvula var. shrevei, and Lithocarpus densiflorus). In the United Kingdom so far, bleeding cankers caused by inner bark infections have been found on Aesculus hippocastanum, Fagus sylvatica, Q. cerris, Q. falcata, and Q. petraea (http://rapra.csl.gov.uk [2005]). Shoot tip dieback (ramorum dieback) and foliar necrosis (ramorum leaf blight) are other diseases caused by the pathogen on understory and ornamental plants (3). Inoculum is produced on infected shoots and leaves of foliar hosts but not on bole cankers (1). Foliar hosts are thus critical in initiating and maintaining epidemics of tree mortality resulting from lethal bark cankers. Ramorum dieback and blight occurs in Europe on genera Rhododendron, Camellia, Kalmia, Pieris, and Viburnum (http://rapra.csl.gov.uk [2005]), and now we report these diseases on foliage and shoots of holm oaks (Quercus ilex) in Cornwall (UK). First discovered in November 2003, infected young leaves had a water-soaked, dull gray appearance, and petioles were blackened. Lesions started at leaf margins, tips, or petioles, often progressing into the midrib veins. Initial infections also occurred on shoots and extended into the petioles. If shoots were infected, they were blackened at first, but later in the season clusters of dry, dead leaves and twigs characterized branch tips. Infected mature leaves bore dry, reddish-brown, restricted lesions. P. ramorum (A1 sexual compatibility type belonging to the European population) was isolated and confirmed by morphological studies, ITS sequence (GenBank Accession No. AY924253), and amplified fragment length polymorphism analyses. Lesions developed on detached leaves dipped for 10 sec in inoculum (4 × 105 zoospores per ml) and incubated in moist chambers at 20°C for 6 days (2). Two isolates were used (four leaves per isolate). The pathogen was reisolated, and the tests were repeated twice. Koch's postulates were also successfully completed once on foliage attached to saplings. To our knowledge, this is the first report of P. ramorum on holm oak. So far, at least 24 holm oaks are infected at various woodland and garden sites in the United Kingdom; infected rhododendrons have also been found at these sites. P. ramorum has also been recorded on saplings in nurseries. The high sporulation potential, the evergreen nature of leaves, and susceptible shoots indicate that holm oak could be a significant source of inoculum for other hosts.
APSAPSThe following values have no corresponding Zotero field: pub-location: 3340 PILOT KNOB ROAD, ST PAUL, MN 55121 USA publisher: AMER PHYTOPATHOLOGICAL SOC
Keywords: pathogens; Phytophthora ramorum; Quercus ilex

European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi - Brasier, C. M.; SCOTT, J. K. (EPPO Bulletin, 1994)
Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress-related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land-use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamomi. Under conditions of global warming the survival and degree of root disease caused by this fungus seems likely to be enhanced, while the host range of the organism might also be increased. Application of the CLIMEX climate-matching program suggests that with a mean increase in temperatures of 1.5–3°C the fungus might considerably increase its disease activity in its existing locations, and to some extent spread northwards and eastwards. However, it seems unlikely to become significantly active in areas of Europe with colder winters such as parts of Scandinavia, Russia and the central Danube. The predictive value of research on major environmental problems such as oak declines could be enhanced by more highly coordinated European forestry research programmes.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Oak decline; phytophthora cinnamomi; range expansion (PG); root disease

Evidence for Phytophthora cinnamomi involvement in Iberian oak decline - Brasier, C. M.; ROBREDO, F.; FERRAZ, J. F. P. (Plant Pathology, 1993)
Rapid and sometimes extensive mortality and decline of oak, principally Quercus suber and Q. ilex, has occurred in parts of southern Spain and Portugal in recent decades. We report here isolation of the aggressive root pathogen Phytophthora cinnamomi from roots of diseased oaks or from soil at eleven out of thirteen decline foci examined. It is proposed that the introduction and spread of P. cinnamomi may be a major factor in the Iberian oak decline, interacting with drought and other site factors, and leading to stress-related attacks by insects and other fungi. By analogy, it may also be involved in the similar oak declines occurring elsewhere on the Mediterranean.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought; Oak decline; phytophthora cinnamomi; site factors (PG)